Associations Between Sleep‐Disordered Breathing, Nocturnal Hypoxemia, and Subsequent Cognitive Decline in Older Community‐Dwelling Men: The Osteoporotic Fractures in Men Sleep Study. Issue 3 (2nd March 2015) - Blackwell, Terri; Yaffe, Kristine; Laffan, Alison; Redline, Susan; Ancoli‐Israel, Sonia; Ensrud, Kristine E.; Song, Yeonsu; Stone, Katie L.; ,
Abstract : Objectives: To determine whether sleep‐disordered breathing (SDB), a group of disorders common in older adults characterized by breathing pauses during sleep often accompanied by hypoxemia, is associated with cognitive decline. Design: Population‐based longitudinal study. Setting: Six centers in the United States. Participants: Community‐dwelling older men (N = 2, 636; aged 76.0 ± 5.3) without probable mild cognitive impairment or dementia followed for 3.4 ± 0.5 years. Measurements: SDB was measured using in‐home polysomnography: nocturnal hypoxemia (≥1% of sleep time with oxygen saturation (SaO2 ) <90%, oxygen desaturation index (ODI: number of oxygen desaturations of ≥3% per hour of sleep)) and apnea–hypopnea index (AHI, number of apneas and hypopneas at ≥3% desaturation per hour of sleep). Cognitive decline was measured using the Modified Mini‐Mental State Examination (3MS) and the Trail‐Making Test Part B (Trails B) at baseline and two follow‐up points. Associations between predictors and cognitive decline were examined using linear mixed models adjusted for multiple confounders. Models were further adjusted for potential mediators (sleep duration, sleep fragmentation, resting SaO2 ). Results: Nocturnal hypoxemia was related to greater decline on the 3MS. Men with 1% or more of sleep time with SaO2 less than 90% had an adjusted annualized decline of 0.43 points, compared with 0.25 for men in the reference group ( P  =   .003). For each 5‐point increase in ODI, there was an average annualized decline of 0.36 points ( P  =   .01). Results were robust to further adjustment for potential mediators. The association between AHI and cognitive decline did not reach significance. No associations were seen with SDB and decline on the Trails B. Conclusion: In older community‐dwelling men, there was a modest association between nocturnal hypoxemia and global cognitive decline, suggesting the importance of overnight oxygenation for cognitive function.